Molecular genetic characteristics of patients with hypertrophic cardiomyopathy: a review - Yu. A. Yus'kiv; A. A. Chernova; S. Yu. Nikulina; D. B. Drobot; V. A. Sakovich; O. O. Kardashova (Российский кардиологический журнал, 2024)
Hypertrophic cardiomyopathy (HCM) is a diagnosis established in each case of left ventricular hypertrophy of unknown origin when the left ventricular wall is greater than or equal to 15 mm in one or more myocardial segments according to imaging data. The hereditary nature of HCM is no longer in doubt. But successful verification of HCM using genetic tests is 60% of cases. This fact makes it possible to believe that a search for new predictor genes for HCM is necessary. The review presents current literature data on mutations in genes associated with hypertrophic cardiomyopathy.